KEMAMPUAN MEMBACA PEMAHAMAN DENGAN STRATEGI THE COGNITIVE ACADEMIC LANGUAGE LEARNING APPROACH (CALLA) BERBASIS KEARIFAN LOKAL SISWA KELAS VII SMP NEGERI 18 PADANG - Witri Annisa; Rio Rinaldi (Universitas Andalas, 2017)
The result of the research ”Programme for International Student Assesment (PISA)” states that student reading interest get in 57th position from 65 countries. It means that the students reading interest in Indonesia is still low. It will influence the ability of student reading comprehension Like what happen in SMP Negeri 18 Padang. One of the way to solve this problem is CALLA strategy based on local wisdom. This strategy is carried out through five stages: preparation, presentation, practice, evaluation, and follow-up. The aim of this research is to describe the learning process and the ability of student reading comprehension in class seven in SMP Negeri 18 Padang using CALLA strategy based on the local wisdom. This reasearch is quantitative and description method. The result of this research is the ability of student reading comprehension class seven in SMPN 18 Padang progresses, pretest mark is 73,53 and postest mark is 84,03. It means that CALLA strategy based on the local wisdom can increase the ability of student reading comprehension. Learning by applying this strategy can make student easier understanding the text. Keywords: CALLA Strategy, reading comprehension learning, local wisdom